HUBUNGAN ANTARA MOTIVASI BERPRESTASI DAN REGULASI DIRI DENGAN KEMAMPUAN MENGAMBIL KEPUTUSAN - Nasiyati, Nur (Indonesian Journal of Guidance and Counseling: Theory and Application, 2014)
This study was conducted based on the phenomena that exist in UKM The Green Scientists Society, Faculty of Education, State University of Semarang which shows that 12.82% functionaries who have high achievement motivation, low self-regulation, and the ability to make decisions is low. The purpose of this study is to determine the relationship between achievement motivation and self-regulation with the ability to make decisions. This study belongs to the ex post facto research with a quantitative correlation method. Researchers conducted a population study with 39 functionaries. Data collection using the scales ability to make decisions, achievement motivation scale, and the scale of self-regulation. The data analysis technique used is the technique of multiple linear regression analysis. The results of this study indicate that there is a significant relationship between achievement motivation and self-regulation with the ability to make decisions, obtained Fcount 30.191 with a significance level of 0.000 <0.05 means that Ho is rejected and Ha accepted. Based on the results, it can be predicted that achievement motivation and self-regulation can increase a persons ability to make decisions.